1994
DOI: 10.1109/25.312809
|View full text |Cite
|
Sign up to set email alerts
|

Path loss, delay spread, and outage models as functions of antenna height for microcellular system design

Abstract: This paper presents results of wide-band path loss and delay spread measurements for five representative microcel-Mar environments in the San Francisco Bay area at 1900 MHz. Measurements were made with a wide-band channel sounder using a 100-ns probing pulse. Base station antenna heights of 3.7 m, 8.5 m, and 13.3 m were tested with a mobile receiver antenna height of 1.7 m to emulate a typical microcellular scenario. The results presented in this paper provide insight into the satistical distributions of measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(124 citation statements)
references
References 15 publications
8
110
0
6
Order By: Relevance
“…al. [28], and Maciel and Bertoni [53] make similar observations. Maciel and Bertoni see a similar qualitative cell shape when performing ray-tracing simulations for signals at 900 MHz with uniform building structures on a regular street grid.…”
Section: Related Worksupporting
confidence: 63%
“…al. [28], and Maciel and Bertoni [53] make similar observations. Maciel and Bertoni see a similar qualitative cell shape when performing ray-tracing simulations for signals at 900 MHz with uniform building structures on a regular street grid.…”
Section: Related Worksupporting
confidence: 63%
“…The shadowing per cluster is characterized by the shape of the probability density function (assumed to be lognormal), the variance (typically on the order of 3-10 dB), and the coherence length anywhere from 5 to 100 m). The pathloss is assumed to follow the model of COST231 [33] for macrocells, and [37] for microcells.…”
Section: B Parameter Values and Capacities For Macro-and Microcellsmentioning
confidence: 99%
“…Studies conducted in the San Francisco Bay area by Feuerstein et al [7] have shown an increased radio wave propagation loss when the Freznel zone, described in the introduction, is partially obstructed.…”
Section: Requirements For Effective Radio Transmissionmentioning
confidence: 99%